BYSL Promotes Glioblastoma Cell Migration, Invasion, and Mesenchymal Transition Through the GSK-3β/β-Catenin Signaling Pathway - Sha, Zhuang; Zhou, Junbo; Wu, Yihao; Zhang, Tong; Li, Cheng; Meng, Qingming; Musunuru, Preethi Priyanka; You, Fangting; Wu, Yue; Yu, Rutong; Gao, Shangfeng (Frontiers in Oncology, 2020)
BYSL, which encodes the human bystin protein, is a sensitive marker for astrocyte proliferation during brain damage and inflammation. Previous studies have revealed that BYSL has important roles in embryo implantation and prostate cancer infiltration. However, the role and mechanism of BYSL in glioblastoma (GBM) cell migration and invasion remain unknown. We found that knockdown of BYSL inhibited cell migration and invasion, downregulated the expression of mesenchymal markers (e.g., β-catenin and N-cadherin), and upregulated the expression of epithelial marker E-cadherin in GBM cell lines. Overexpression of BYSL promoted GBM cell migration, invasion, and epithelial-mesenchymal transition (EMT). In addition, the role of BYSL in promoting EMT was further confirmed in a glioma stem cell line derived from a GBM patient. Mechanistically, overexpression of BYSL increased the phosphorylation of GSK-3β and the nuclear distribution of β-catenin. Inhibition of GSK-3β by 1-Azakenpaullone could partially reverse the effects of BYSL downregulation on the transcriptional activity of β-catenin, the expression of EMT markers, and GBM cell migration/invasion. Moreover, immunohistochemical analysis showed strong expression of BYSL in GBM tissues, which was positively correlated with markers of mesenchymal GBM. These results suggest that BYSL promotes GBM cell migration, invasion, and EMT through the GSK-3β/β-catenin signaling pathway.